Source cell-type epigenetic memory persists in induced pluripotent cells but is lost in subsequently derived germline cells - Lin, Yu-Huey; Lehle, Jake D.; McCarrey, John R. (Frontiers in Cell and Developmental Biology, 2024)
Introduction -Retention of source cell-type epigenetic memory may mitigate the potential for induced pluripotent stem cells (iPSCs) to fully achieve transitions in cell fate in vitro. While this may not preclude the use of iPSC-derived somatic cell types for therapeutic applications, it becomes a major concern impacting the potential use of iPSC-derived germline cell types for reproductive applications. The transition from a source somatic cell type to iPSCs and then on to germ-cell like cells (GCLCs) recapitulates two major epigenetic reprogramming events that normally occur during development in vivo -embryonic reprogramming in the epiblast and germline reprogramming in primordial germ cells (PGCs). We examined the extent of epigenetic and transcriptomic memory persisting first during the transition from differentiated source cell types to iPSCs, and then during the transition from iPSCs to PGC-like cells (PGCLCs).Methods -We derived iPSCs from four differentiated mouse cell types including two somatic and two germ cell types and tested the extent to which each resulting iPSC line resembled a) a validated ES cell reference line, and b) their respective source cell types, on the basis of genome-wide gene expression and DNA methylation patterns. We then induced each iPSC line to form PGCLCs, and assessed epigenomic and transcriptomic memory in each compared to endogenous PGCs/M-prospermatogonia.-In each iPSC line, we found residual gene expression and epigenetic programming patterns characteristic of the corresponding source differentiated cell type from which each was derived.However, upon deriving PGCLCs, we found very little evidence of lingering epigenetic or transcriptomic memory of the original source cell type.Discussion -This result indicates that derivation of iPSCs and then GCLCs from differentiated source cell types in vitro recapitulates the two-phase epigenetic reprogramming that normally occurs in vivo, and that, to a significant extent, germline cell types derived in vitro from pluripotent cells accurately recapitulate epigenetic programming and gene expression patterns corresponding to equivalent endogenous germ cell types, suggesting that they have the potential to form the basis of in vitro gametogenesis as a useful therapeutic strategy for treatment of infertility.